Trueness of intraoral scanners according to subgingival depth of abutment for fixed prosthesis - Young-Tak Son; KeunBaDa Son; Kyu-Bok Lee (Scientific Reports, 2022)
Abstract This study aimed to compare the trueness of intraoral scanners (IOSs) according to the subgingival finish line depth of tooth preparation for fixed prostheses. The prepared maxillary right first molar was fabricated by using ceramic material. A computer-aided design (CAD) reference model (CRM) of the abutment was obtained by using a contact scanner. The subgingival finish line was located according to the depth at 0-mm, 0.25-mm, 0.5-mm, 0.75-mm, and 1-mm. CAD test models (CTMs) were obtained by using 2 IOSs (i500 and CS3600). CRM and CTM were superimposed and analyzed (Geomagic control X). The one-way analysis of variance (ANOVA) was used to compare the trueness according to the subgingival finish line depth. The paired t test was used to compare the trueness of IOSs with and without gingival retraction (α = .05). When the gingival displacement code was not used, it was observed that the trueness of both IOSs decreased significantly as the depth of the subgingival finish line increased (P < 0.001). When the subgingival finish line was positioned deeper than 0.5-mm, the trueness of both IOSs exceeded 100 µm in the marginal region. When the gingival displacement cord was used, the trueness of both IOSs did not exceed 100 µm regardless of the subgingival finish line depth. When gingival cord was used, it showed significantly higher trueness than when not used (P < 0.001). When the gingival displacement cord was not used, the trueness of IOSs decreased as the subgingival finish line depth increased. But the use of the gingival displacement cord improved the scanning trueness by 90%. Thus, it is necessary to use the gingival displacement cord according to the clinical situation to improve scan trueness at the subgingival finish line.